Differential accumulation of antioxidant mRNAs in Arabidopsis thaliana exposed to ozone. - Conklin, P L (1995)
Antioxidant isoenzymes function to eliminate free radicals and are localized to several different subcellular compartments within the plant cell. In Arabidopsis thaliana exposed to ozone (O3), we have monitored the accumulation of mRNAs encoding both cytosolic and chloroplastic antioxidant isoenzymes. Two different O3 exposure protocols yielded similar results. Upon O3 exposure, the steady-state levels of three mRNAs encoding cytosolic antioxidant isoenzymes (ascorbate peroxidase, copper/zinc superoxide dismutase, and glutathione S-transferase) increase. The glutathione S-transferase mRNA responds very quickly to the oxidative stress (2-fold increase in 30 min) and is elevated to very high levels, especially in plants grown with a 16-h photoperiod. In contrast, O3 exposure causes a decline in the levels of two chloroplastic antioxidant mRNAs (iron superoxide dismutase and glutathione reductase) and two photosynthetic protein mRNAs (chlorophyll a/b-binding protein and ribulose-1,5-bisphosphate carboxylase/oxygenase small subunit). We show that this decline does not include all mRNAs encoding chloroplast-targeted proteins, since O3 causes an elevation of mRNA encoding the chloroplast-localized tryptophan biosynthetic enzyme phosphoribosylanthranilate transferase. Two alternative hypotheses that could explain this differential mRNA accumulation in response to O3 are discussed.